The use of teaching props to improve mathematics learning outcomes in number pattern material in STEM village Yogyakarta - Fika Ariana; Muhammad Prayito; Nurina Happy; Wisnuningtyas Wirani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
Since mathematics is an abstract discipline, it is necessary to understand context when learning. This pilot study at SDN 1 Kentungan, a "STEM Village" in Joho Village, Yogyakarta, aims to determine the impact of stick-board teaching aids on second-grade students' mathematics learning results in number patterns. The devices used for collecting data include pre-tests and post-tests, interview sheets, observation sheets, and other methods. Meanwhile, the small set of test participants consisted of two SD N 1 Kentungan class II students who attended the STEM Village in Kampung, Joho. The conclusions of this descriptive study show the following: (1) the way teaching tools are used affects how number patterns are taught to primary school pupils; when instructional aids are utilized to assist students in learning a subject more easily and contextually, they are guided by more than just formulas. (2) Students perform better on their pretest and posttest. (3) Students' understanding improves after using visual aids compared to before using them. (4) Students become more curious and engaged in the learning process. The results of the study suggest that class II students at SDN 1 Kentungan benefit from using instructional aids, which are regarded as compelling and well-done.